Achievements and Challenges of Graphene Chemical Vapor Deposition Growth. (11th May 2022) - Liu, Fengning; Li, Pai; An, Hao; Peng, Peng; McLean, Ben; Ding, Feng
Abstract: Graphene, since the first successful exfoliation of graphite, has continuously attracted attention due to its remarkable properties and applications. Recently, the research focus on graphene synthesis has been directed to the controllable synthesis of large‐area and high‐quality graphene. In the last decade, there has been great progress in the chemical vapor deposition (CVD) growth of graphene. Theoretical investigations have led to an enhanced understanding of puzzles on hydrocarbon species stability, key reaction pathways, the role of hydrogen gas, the morphology of graphene islands, and the alignment of graphene on substrates. Experimentally, high‐quality graphene is epitaxially grown on both insulating and metal substrates. Progress has also been reported on low‐temperature graphene growth and on controlling the thickness and stacking of graphene layers. In this review, the authors summarize the previous theoretical and experimental studies on graphene CVD growth and discuss the future challenges on the growth of graphene i) on insulating substrates, ii) at low temperature, iii) with controllable thickness, and iv) with selected stacking twist angles. The authors assert that the key to the continuous advancement of graphene growth is the synergy of experimental and theoretical investigations. Abstract : Huge achievements have been made in graphene chemical vapor deposition (CVD) growth. This review systematical summarizes the current progresses in four research directions, including theoretical study of graphene CVD growth, direct growth on insulating substrates, low temperature growth, layer number, and stacking‐angle controlled growth. Finally, the future research directions of graphene are discussed.